2023
DOI: 10.1007/s40847-023-00236-1
|View full text |Cite
|
Sign up to set email alerts
|

Digital divide and access to online education: new evidence from Tamil Nadu, India

Abstract: The pandemic and the long closure of educational institutions have changed the learning and teaching practices across the globe. A massive and unplanned shift towards online education with unequal access to digital infrastructure deepens the existing digital divide and socio-economic inequalities. Tamil Nadu Covid Pulse Survey shows the state’s commitment to strengthening evidence-based policymaking and continuing its welfare tradition including its efforts to provide uninterrupted education during the crisis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The shift to virtual learning could deviate from students' familiar learning environment, and negatively influence their levels of engagement. Another notable reason is the technology familiarity [20]. Foreign-trained residents might come from countries where digital infrastructure is less developed, so they may have fewer online learning experiences in their home countries and the transition to online learning would be more challenging for them as they need additional time to be familiar with online learning tools.…”
Section: Residents Obtained Dental Degrees Outside Of the Us/canadamentioning
confidence: 99%
“…The shift to virtual learning could deviate from students' familiar learning environment, and negatively influence their levels of engagement. Another notable reason is the technology familiarity [20]. Foreign-trained residents might come from countries where digital infrastructure is less developed, so they may have fewer online learning experiences in their home countries and the transition to online learning would be more challenging for them as they need additional time to be familiar with online learning tools.…”
Section: Residents Obtained Dental Degrees Outside Of the Us/canadamentioning
confidence: 99%
“…With the advent of online education, we have celebrated a pivotal development in the quest to democratize access to learning, heralded for its potential to transcend geographical, socio-economic, and cultural barriers that have traditionally impeded equitable educational opportunities (Iivari, Sharma, & Ventä-Olkkonen, 2020;Jafar, Ananthpur, & Venkatachalam, 2023). Despite its transformative promise, the deployment of online education across various landscapes has illuminated stark disparities, highlighting a complex web of challenges that hinder its effectiveness in fostering educational equity (Bhattacharya, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The abrupt shift to online learning led many impoverished students to struggle. Research in India (Jafar et al, 2023) and Pakistan (Ullah, 2022) revealed that vulnerable students could not access appropriate technology or continue their studies like their privileged peers. In Thailand, the Equitable Education Fund (EEF, 2021) reported that 271,888 students lacked digital devices for online study and 43,013 students from disadvantaged households were forced to drop out of school due to parental loss of income and unemployment.…”
Section: Introductionmentioning
confidence: 99%